2021
DOI: 10.1007/s00431-021-04124-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgG levels in children 6 months after SARS-CoV-2 infection and comparison with adults

Abstract: Since the outbreak of SARS-CoV-2 among the population has occurred quite recently, there is a lack of evidence on the long-term duration of antibody response, especially in children. It is therefore crucial to clarify this aspect, considering its implications in the development of successful surveillance strategies, therapies, and vaccinations. The aim of this study was to assess the antibody response in a children group after SARS-CoV-2 infection, and to compare it with that of their parents affected by SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
(35 reference statements)
2
28
1
Order By: Relevance
“…Primarily, along with a non-severe spread of SARS-CoV-2 infection in children [ 23 , 24 ], we observed a drastic reduction in the incidence of the main pediatric diseases caused by atopy and common seasonal bacteria and viruses. Not surprisingly, in 2020 the typical increase in consultations and hospital admissions for respiratory syncytial virus (RSV) and influenza viruses did not occur during the winter season [ 13 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, along with a non-severe spread of SARS-CoV-2 infection in children [ 23 , 24 ], we observed a drastic reduction in the incidence of the main pediatric diseases caused by atopy and common seasonal bacteria and viruses. Not surprisingly, in 2020 the typical increase in consultations and hospital admissions for respiratory syncytial virus (RSV) and influenza viruses did not occur during the winter season [ 13 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited data are available regarding the persistence of antibody responses in children. In a small cohort of children, anti-SARS-CoV-2 IgG declined six months after infection with lower levels than their infected parents at the same time point [61]. In a recent larger cohort study, children and adolescents showed high and durable antibody responses to SARS-CoV-2, following mild or asymptomatic infection [62].…”
Section: Immune Response To Sars-cov-2 Infection In Childrenmentioning
confidence: 92%
“…In Switzerland, a serosurvey showed a significantly lower seroprevalence among children aged 5-9 years (0.8%) and a lower risk of seropositivity compared to individuals aged 20-49 years (RR 0.32) [116], therefore confirming the studies on attack rate. Only few studies have been published on this topic, and it will also be important to assess the durability of antibodies following SARS-CoV-2 infection in children for the interpretation of seroprevalence studies [61,62].…”
Section: Sars-cov-2 Transmission By Children In Household Studiesmentioning
confidence: 99%
“…The first home visit takes place on day 4, 5 or 6 (=t1) after testing date of the index case (t0). These home visits include (1) study information, informed consent, (2) collection of a combined mouth and nose swab, a saliva sample and capillary blood sample which can be used for a retrospective assessment of an earlier SARS-CoV-2 infection ( 19 ). This blood sample is taken from the fingertip and dried on specific paper for transport (dried blood spot).…”
Section: Methods and Analysismentioning
confidence: 99%